The Impact of Canva-Based Instructional Media on Enhancing Students’ English Ecovocabulary at SMP Putri Khodijah Sumbawa - Suparman, Suparman; Ridwan, Ridwan (e-Journal of Linguistics, 2025)
This study examines the effect of implementing Canva-based instructional media on improving the English vocabulary proficiency of students at SMP Putri Khodijah Sumbawa. The objectives of this study are as follows: (1) to analyze the significant effect of Canva-based instructional media on enhancing students’ English vocabulary skills at SMP Putri Khodijah Sumbawa, and (2) to identify students’ perceptions of the use of Canva-based instructional media in English learning at SMP Putri Khodijah Sumbawa. This study employed a quantitative method with a quasi-experimental design. The participants consisted of 28 students who were divided into an experimental group and a control group, with 14 students in each group. The instruments used for data collection were pre-tests, post-tests, and questionnaires. The data were then analyzed using SPSS version 26. The results indicate that: (1) there is a positive and significant effect of the use of Canva-based instructional media on improving students’ English vocabulary skills at SMP Putri Khodijah Sumbawa. This is evidenced by the results of the paired-samples t-test in the experimental group and the independent-samples t-test between the experimental and control groups, which yielded significance values of 0.000 and 0.002 respectively, both of which are lower than 0.05; and (2) the results of the questionnaire on students’ perceptions of the use of Canva show highly positive responses, with the highest mean scores on items P3, P5, and P10, each reaching 4.71 (on a scale of 5), and low standard deviations, indicating consistent perceptions among students. It can therefore be concluded that the implementation of Canva-based instructional media not only improves students’ vocabulary mastery but also enhances their motivation and engagement in the learning process.